Chapter 3 Time Depth Jean Epstein, Michel Serres and Operational Model Time - Rosol, Christoph (Taylor & Francis, 2021)
This volume presents an interdisciplinary dialogue between sociology, geography, political sciences, history, and literary, cultural and media studies. Together, they contribute to current debates on the (re-)imagining of forms of human responsibility that meet the challenges created by humanity entering an age of scalar complexity.